2q37 deletion syndrome in a Colombian patient with macrocephaly: a case report - Sebastian Giraldo-Ocampo; Harry Pachajoa (BMC, 2022)
Abstract Background 2q37 deletion syndrome is a rare autosomal dominant disorder caused by deletions in the 2q37 cytobands leading to developmental delay, intellectual disability, behavioral abnormalities and dysmorphic craniofacial features with more than 115 patients described worldwide. Case presentation We describe a Colombian 3-year-old patient with verbal communication delay, umbilical hernia, facial dysmorphic features, hypotonia, and macrocephaly with normal magnetic resonance imaging. Microarray-based comparative genomic hybridization revealed a 5.9 Mb deletion in the 2q37.2 and 2q37.3 regions, eliminating 60 protein-coding genes in one of her chromosomes 2 and allowing the diagnosis of 2q37 deletion syndrome in this patient. Therapeutic interventions so far were the surgical correction of the umbilical hernia. Conclusions Genetic tests are important tools for the diagnosis of clinically complex and infrequent conditions but also for timely diagnosis that allows appropriate surveillance, interventions, and genetic counseling. This case also provides information for expanding the phenotypical and genetic characterization of 2q37 deletion syndrome.